Analysis and design of double layer space grid system truss / Abdul Aziz Yusoff - Yusoff, Abdul Aziz (1982)
This project report contains the analysis and design of a double layered space frame structures. The geometric forms used in this analysis and design were the two way and three way systems referred to as the square on square offset and octahedra-tetrahedra grid respectively. All analysis were made on the results obtained from the ICL 1900 Series SPACEFRAME package program which is available at ITM Computer Centre. The method of calculation used by package is based on one described by R.K Livesley in Analysis of Rigid Frames by an Electronic Digital Computer. The purpose of the work is to introduce one of the important applications of the technique in the analysis of symmetry structures in which the running time of the computer package program is reduced. In this technique, it is enough to solve half or a quarter of the structure and then the internal forces and displacement of the other portion are found by symmetry. Therefore a symmetry structures having large number of joints and members can be analysed by considering only portion of the structure. This work also covers the studies of forces in the members by varying the spans, the effect of changing support conditions, the optimum method of design by varying the size of members and finally to define the limitations in analysing space structures by using ICL 1900 Series SPACEFRAME package program.